Effects of the Spanish influenza pandemic of 1918 - 19 on later life mortality of Norwegian cohorts born about 1900 - Svenn-Erik Mamelund (University of Oslo, Department of Economics, 2003)
By using Age-Period-Cohort analysis the paper shows that Norwegian male and female cohorts born about 1900 have experienced significantly higher all-cause mortality in middle and old ages relative to “neighbor” cohorts. In a widely cited study, Horiuchi suggests that only males from belligerent countries who were adolescents during WW I exhibit this cohort effect. The finding in this paper demonstrates that Horiuchi's explanation may be incomplete.The search for explanations for neutral Norway must clearly go beyond the direct (soldiers wounded physically and mentally) and indirect effects (rationing of food) of WW I on laterlife mortality. This paper suggests that Spanish Influenza 1918-19 is the most important of several possible factors priming the Norwegian cohorts. A large proportion of the cohorts considered contracted Spanish Influenza, but only a small proportion died of it immediately.The net effect on later life mortality is thus assumed to be that of debilitation.
Keywords: J00; L12; 330; Spanish Influenza 1918-19; morbidity; mortality; debilitation; selection; APCanalysis; cohort effects; Norway; Krankheit; Sterblichkeit; Norwegen; Kohortenanalyse